2017
DOI: 10.3389/fpsyg.2017.01181
|View full text |Cite
|
Sign up to set email alerts
|

Parental Education and Aggressive Behavior in Children: A Moderated-Mediation Model for Inhibitory Control and Gender

Abstract: Aggressive behaviors are highly prevalent in children. Given their negative consequences, it is necessary to look for protective factors that prevent or reduce their progress in early development before they become highly unshakable. With a sample of 147 children, the present study aimed to assess the relation between parental education and inhibitory control in the aggressive behavior of children aged from 7 to 10 years. The participants completed a go/no-go task to assess inhibitory control, whilst their par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
0
17
0
5
Order By: Relevance
“…Thus, despite the fact that results are not always consistent, the majority of studies find gender influences in inhibitory control and aggressive behavior, thereby underlining the importance of considering gender as a possible moderator when examining mediation effects of inhibitory control in risk-aggression associations (Cabello, Gutierrez-Cobo, & Fernandez-Berrocal, 2017;Granero et al, 2015). Cabello et al (2017) examined the role of gender in relation to parental educational level, inhibitory control, and aggression in a school age sample. It was found that inhibitory control mediated the negative relation between parental educational level and teacher-rated aggression, but only for boys.…”
Section: Influence Of Gendermentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, despite the fact that results are not always consistent, the majority of studies find gender influences in inhibitory control and aggressive behavior, thereby underlining the importance of considering gender as a possible moderator when examining mediation effects of inhibitory control in risk-aggression associations (Cabello, Gutierrez-Cobo, & Fernandez-Berrocal, 2017;Granero et al, 2015). Cabello et al (2017) examined the role of gender in relation to parental educational level, inhibitory control, and aggression in a school age sample. It was found that inhibitory control mediated the negative relation between parental educational level and teacher-rated aggression, but only for boys.…”
Section: Influence Of Gendermentioning
confidence: 99%
“…Thus, despite the fact that results are not always consistent, the majority of studies find gender influences in inhibitory control and aggressive behavior, thereby underlining the importance of considering gender as a possible moderator when examining mediation effects of inhibitory control in risk–aggression associations (Cabello, Gutierrez‐Cobo, & Fernandez‐Berrocal, ; Granero et al., ). Cabello et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, this psychologist's professional knowledge, expressed in his ST, is in line with studies on the link between several parental traits and their children's behavior (e.g. Cabello, Gutiérrez-Cobo, & Fernández-Berrocal, 2017); specifically, the role of parents' emotions and their influence on child disruptive behavior problems has also been studied (though not in Latin America) (e.g. Stormshak, Bierman, McMahon, Lengua & Conduct Problems Prevention Research Group, 2000).…”
Section: Discussionmentioning
confidence: 65%
“…Por otro parte, en otros trabajos se relacionan los estilos educativos parentales con la emoción de ira y las conductas agresivas (Cabello, Gutiérrez-Cobo y Fernández-Berrocal, 2017; De la Torre-Cruz, García-Linares y Casanova-Arias, 2014; Pelegrín y Garcés de los Fayos, 2009). De manera que, De la Torre-Cruz et al (2014) mostraron que los padres autoritarios, con bajo nivel de afecto y con alto nivel de control, se relacionan con la expresión de conductas agresivas.…”
Section: Introductionunclassified